A nano graphene oxide/α-zirconium phosphate hybrid for rigid polyvinyl chloride foams with simultaneously improved mechanical strengths, smoke suppression, flame retardancy and thermal stability. (June 2019) - Wang, Zhengzhou; Huang, Zhenyu; Li, Xiaoyan; Zhou, Jian-an
Abstract: A nano graphene oxide/α-zirconium phosphate (α-ZrP) hybrid (GOZP) was synthesized by an in-situ technique, and characterized by XRD, FTIR, SEM, TEM, etc. Rigid polyvinyl chloride (RPVC) foams containing GOZP exhibit high mechanical, flame retardant and smoke suppressive properties. The compressive and flexural strengths of sample RPVC/GOZP3 with 3 phr GOZP increase by 28.6% and 45.2%, respectively compared to those of pure RPVC foam. The limiting oxygen index (29.5%) of sample RPVC/GOZP3 is higher than that (27.5%) of pure RPVC foam. The cone calorimeter test results demonstrate that peak heat release rate, total heat release and total smoke production of sample RPVC/GOZP3 decrease by 13%, 24% and 59%, respectively compared with the ones of pure RPVC foam. Moreover, sample RPVC/GOZP3 shows a higher thermal stability than pure RPVC foam.